ABH and Lewis blood group systems and their relation to diagnosis and risk of Helicobacter pylori infection. (March 2021) - de Oliveira, Isabella Almeida; Corvelo, Tereza Cristina de Oliveira
Abstract: Background: Helicobacter pylori infection occurs in 50% of the world's population and represents a major risk factor for chronic gastritis, gastroduodenal ulcer and gastric cancer in developed and developing countries. The distribution of H. pylori virulence factors is diverse and varies geographically, such as the CagA and VacA genes, which have revealed association with disease status. Some findings show increased frequencies of these diseases in O Le (a-b +) and A Le (a-b +) blood type individuals, but other studies not found any relationship between these blood groups and H. pylori infection. Aim: This study aimed to elucidate probable controversies described in the relationship between the ABH/Lewis blood groups and H. pylori, contributing to the severity of gastric diseases in northern the population of Belém -Pará.-Brazil. Methods: This cross-sectional study included 288 samples of patients separate into two groups with gastric cancer and chronic gastritis. Blood, saliva, and gastric biopsy were analyzed using modified Gram and hematoxylin-eosin staining techniques, the enzyme immunoassay Elisa and Multiplex PCR. The antigens expression of ABH and Lewis systems was determined through Dot-ELISA and direct hemagglutination. Proportions were compared in univariate analysis, while the relation between putative risk factors including H. pylori status and ABO/Lewis phenotype was performed using multivariable logistic regression analyses, P-value < 0.05 was considered significant. Results: The findings of this study demonstrate that the likelihood of developing gastric cancer increases threefold if the individual is from A1 Le (a-b +) blood group, has premalignant changes, and infection with H. pylori virulent strains ( cagA +/ vacA  + s1m1). Conclusion: Therefore, this study found a significant association between ABO and Lewis phenotypes and H. pylori cagA status into the relevance of the development of gastric carcinogenesis. Graphical abstract: Image 1 Highlights: The H. pylori do not grow in damaged areas, influencing the histological diagnosis. The host genetic background has impact in the severity of gastric alterations. The O/A2 Lewis b (a-b+) phenotypes facilitates H. pylori adhesion in gastric mucosa.